Role of Pie Crusting Technique on Soft Tissues in Preventing Soft Tissue Complications Compared to Conventional Closure of Wound in Fractures of Distal Tibia (PILON) and Fibula - Ahmad, Rana Shahbaz; Amin, Muhammad Suhail; Hassan, Bushra; Rathore, Muhammad Omar; Rehan, Muhammad; Javid, Mohsin (Pakistan Armed Forces Medical Journal, 2022)
Objective: To demonstrate the effect of performing pie crusting on skin bridging two incisions used for open reduction and fixation to reduce wound complications compared to conventional wound closure.Study Design: Quasi-experimental study.Place and Duration of Study: Department of Orthopedics and Trauma, Combined Military Hospital Rawalpindi from Jan to Nov 2020.Methodology: Forty-seven patients, managed primarily with open reduction and internal fixation for type-43 fractures per AO/OTA classification, were studied. Group-1 comprised patients in whom the pie crusting technique was used during the closure of the wound. Group-2 included patients in whom conventional closure of the wound was performed. Evaluation of complications in the presence or absence of superficial and deep infection and necrosis was done. The time from injury to surgery was 6 hours to 72 hours. Patients were followed for an average of 12 weeks. Results: In group-1 (pie-crust technique), there were 23 patients, whereas group-2 (classic wound closure) comprised 24 patients. In group-1, only 1 (4%) patient had a superficial infection, and no deep infection was reported. Whereas in group-2, six patients (25%) had superficial infection, and two patients (8%) had the deep infection.Conclusion: Results indicated that pie-crust technique significantly reduces the risk of superficial and deep wound complications compared to classic wound closure because it reduces skin tension and allows the drainage of subcutaneous fluids.